Can Hyaluronic Acid Combined with Chondroitin Sulfate in Viscosupplementation of Knee Osteoarthritis Improve Pain Symptoms and Mobility? - Augustin Dima; Magda Dragosloveanu; Andreea Ramona Romila; Alexandru Cristea; Georgiana Marinică; Alexandru-Tiberiu Dănilă; Alexandru Mandici; Daniel Cojocariu; Robert-Alexandru Vlad; Adriana Ciurba; Magdalena Bîrsan (Biomolecules, 2024)
The objective of the present study was to assess the effect of intra-articular Hyaluronic acid (HA) and Chondroitin sulfate (CS) supplementation (Hialurom® Hondro (HH)) on pain symptoms and joint mobility. In total, 60 mg/mL sodium hyaluronate and 90 mg/mL CS were administered to 21 patients (17 females and 4 males) respecting the in-force requirements, excluding patients with some specific comorbidities. In addition to the clinical study (where the pain intensity (severity) and joint mobility were assessed), rheological characterization was conducted evaluating the following parameters: elastic modulus (G′), loss modulus (G″) oscillatory frequency (fc) at 0.5 Hz and 2.5 Hz, crossover frequency (fc), relaxation time (λ) where it was noticed that the addition of chondroitin sulfate (CS) to sodium hyaluronate (SH) significantly enhances and improves the viscoelastic properties, particularly at higher shear frequencies. A significant decrease in pain intensity felt by the subjects was found, from 7.48 (according to Wong–Baker scale)—pain close to 8 (the patient is unable to perform most activities), to more reduced values of 5.86—at 6 weeks after injection, 4.81—at 3 months after injection, and 5.24—at 6 months after injection, improvements in symptoms was fast and durable. Data related to the evolution of joint mobility show that at 6 weeks after injection, the mobility of joints increased by 17.8% and at 6 months by 35.61%. No serious adverse events were reported with undesired effects so that they would impose additional measures. Better resistance to enzymatic degradation and free radicals could be expected from the synergic combination of sodium hyaluronate and chondroitin sodium sulfate, this having a special importance for the patients, granting them the ability to perform more ample movements and reducing dependency on attendants, thus increasing quality of life.